FAKTOR PENYEBAB RENDAHNYA MINAT BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA KELAS IV SD (STUDI KASUS DI SD X TANJUNG ALAM) - SISKA JUNITA; Safrizal, Safrizal (AL-IHTIRAFIAH: JURNAL ILMIAH PENDIDIKAN GURU MADRASAH IBTIDAIYAH, 2023)
This research is motivated by a situation where researchers see the phenomenon of low interest in learning mathematics in class IV SD X Tanjung Alam students, causing students to be lazy to take part in mathematics learning which results in learning outcomes that are less than optimal. This study aims to determine what factors influence the low interest in learning mathematics in class IV SD X Tanjung Alam. In this study used a qualitative research method with a case study type. The technique of determining informants is carried out with non-probability side through snowball sampling technique. In this study, the researchers chose the informants, namely teachers and fourth grade students at SD X Tanjung Alam. In this research, the researcher is the key instrument in data collection. Researchers are assisted with supporting instruments such as interview guides, observation guidelines, cameras and recording devices. Data collection in this study was carried out in three ways, namely in-depth interviews, observation and documentation studies. For data analysis techniques, researchers used the Miles and Huberman technique which was carried out in four stages. Meanwhile, to guarantee the validity of the data, researchers used triangulation techniques. The findings of this study indicate that the internal factor of learning difficulties experienced by students in grade IV is student interest in learning. While the external factors are inadequate learning facilities and a less conducive learning environment.